KOMUNIKASI INSTRUKSIONAL PELATIH KESENIAN TAMBUA TASA DI SANGGAR BENGKEL SENI BUDAYA KOTA PEKANBARU - Novita Sari; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The art of tambua tasa is one of Minang art that is thick will be custombut still less popular among teenagers especially in big cities like Pekanbaru.Sanggar Bengkel Seni Budaya is one of the studio that still preserves the art oftambua tasa in Pekanbaru. Teaching members to be able and proficient in playingmusical instruments tua tambua is not easy, let alone members come fromdifferent backgrounds and education. Therefore, in the training process, thetrainer uses instructional communication. The purpose of this research is to knowthe method of instructional communication, media, obstacles and verbalcommunication and nonverbal trainer in training the art of tambua.This research uses qualitative research method. The research wasconducted at Art Workshop Studio of Art at Nenas street No. 68 SukajadiPekanbaru. The infroman clearance was done by purposive technique. As for theinformant of this research is one person niniak mamak, two trainers, two membersin Sanggar Bengkel Seni budaya Pekanbaru. Data collection techniques usedduring conducting research is by way of observation, interview anddocumentation. While the validity of data that researchers use is to extend theparticipation, triangulation and reference adequacy.The results show that, in training the art of tambua tasa in SanggarBengkel Seni Budaya, the trainer uses four methods namely command method,practice method, task method and question and answer method. In the meantimeinstructional media used by the trainer is a tool media in the form of blackboard,stick and the instrument itself (tambua and tasa). During the process of arttraining tambua tasa, not apart from the obstacles that certainly can affect theexercise process. The obstacles that occur in Sanggar Bengkel Seni Budaya aretechnical barriers and psychological barriers. During the training process, thetrainer uses verbal communication as well as nonverbal communication. The formof verbal communication used by the trainer of dominant oral communicationusing Minang language. While nonverbal communication used in the form offacial expressions, eye contact, body movement and hand movements and toneintonation.Keywords: instructional communication, tambua tasa